2016
DOI: 10.12930/nacada-15-012
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Community College Students' Perceptions of and Attitudes Toward Intrusive Academic Advising

Abstract: For this study, we analyzed the relationship between intrusive academic advising and community college student success. Utilizing a qualitative, single-case study design, we conducted interviews with 12 students who participated in an intrusive advising program at a large, urban community college in Texas. Analysis of the interview data revealed the benefits, limitations, and contributions to success of intrusive advising. This study addresses a notable gap in the extant literature, as few researchers have pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…The importance of establishing rapport is supported by the relational component of the NACADA (2017) Core Competency Model. Furthermore, advisors echoed the finding from Donaldson et al (2016) that advisor assignment combined with establishing rapport allows an opportunity for more meaningful conversation between advisor and advisee. Rapport between advisor and advisee relates back directly to Earl's (1988) belief that academic integration is a strong factor in persistence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The importance of establishing rapport is supported by the relational component of the NACADA (2017) Core Competency Model. Furthermore, advisors echoed the finding from Donaldson et al (2016) that advisor assignment combined with establishing rapport allows an opportunity for more meaningful conversation between advisor and advisee. Rapport between advisor and advisee relates back directly to Earl's (1988) belief that academic integration is a strong factor in persistence.…”
Section: Discussionmentioning
confidence: 95%
“…In a survey, NACADA (2011b) found that 31.8% of two-year college respondents reported assigning academic advisors, compared to 56.0% of public baccalaureate institution respondents. A study by Donaldson et al (2016) reported that students attributed rapport with an advisor to the assignment of and multiple meetings with a single advisor.…”
Section: Criteria Associated With Eapsmentioning
confidence: 99%
“…The student outputs linked to advising in qualitative studies were transfer progress for community college students, student success for students in an intrusive advising program, and persistence for minority students. Data for each of those outputs were collected through individual interviews (Donaldson et al, 2016;Museus & Ravello, 2010;Packard & Jeffers, 2013).…”
Section: Rq4: Advising and Student Outputsmentioning
confidence: 99%
“…6) Proactive, or intrusive, advising has been found especially beneficial because, using this strategy, advisors approach students to offer insights and options before problematic issues arise (Varney, 2012). Proactive advising is associated with helpseeking behavior and confidence building among students (Donaldson, McKinney, Lee, & Pino, 2016) and improved retention (Rodgers, Blunt, & Trible, 2014).…”
Section: Nontraditional Studentsmentioning
confidence: 99%